2022
DOI: 10.1136/bmjopen-2022-062847
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening ethics committees for health-related research in sub-Saharan Africa: a scoping review

Abstract: ObjectiveHealth-related research in sub-Saharan Africa (SSA) has grown over the years. However, concerns have been raised about the state of research ethics committees (RECs). This scoping review examines the literature on RECs for health-related research in SSA and identifies strategies that have been applied to strengthen the RECs. It focuses on three aspects of RECs: regulatory governance and leadership, administrative and financial capacity and technical capacity of members.DesignA scoping review of publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…This study provides a practical and tangible example of ways in which researchers and ethical review boards can begin the process of change right away. A recent scoping review highlighted the financial, administrative and regulatory barriers to good quality ethical review in low and middle-income countries31; our study provides relevant findings that may be used to address some of these concerns. A collaborative, multidisciplinary research programme in Kenya has successfully implemented a systematic approach to translating contextualised informed consent templates, drawing on community engagement processes within their research programme, which has received positive engagement from researchers and ethics committees 32.…”
Section: Discussionmentioning
confidence: 87%
“…This study provides a practical and tangible example of ways in which researchers and ethical review boards can begin the process of change right away. A recent scoping review highlighted the financial, administrative and regulatory barriers to good quality ethical review in low and middle-income countries31; our study provides relevant findings that may be used to address some of these concerns. A collaborative, multidisciplinary research programme in Kenya has successfully implemented a systematic approach to translating contextualised informed consent templates, drawing on community engagement processes within their research programme, which has received positive engagement from researchers and ethics committees 32.…”
Section: Discussionmentioning
confidence: 87%
“…Participants did not express the need for continuous training for their members who were assumed to be knowledgeable because of their seniority which overlooks the pivot of keeping REC members in line with emerging research ethics topics, such as gene editing or arti cial intelligence. This inconsistency of requiring ethics training has been documented by research in the region by (6) in Jordan and (11) in Sub-Saharan Africa showing that it is not seen to be necessary; while other research studies in Saudi Arabia describe proper training mechanisms and guidance for RECS (7). REC members in Saudi Arabia are required by law (Law of Ethics of Research on Living Created by the National Committee of Bio-Ethics NCBE) to complete training on ethics and regulations in order to be registered (7), which could explain the attention to this training initiative there.…”
Section: Discussionmentioning
confidence: 96%
“…A scoping review of RECs in Sub-Saharan Africa reported challenges in recruiting and retaining REC members due to the high workload involved and the lack of compensation or incentives to participate in meetings or training and impacting the quality of the reviews. Other challenges include poor administration capacity and lack of time and attention to review tasks (11). In order for RECs to conduct the oversight they are entrusted to do, institutions need to provide them with su cient resources to do their work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…citizen scientists). For instance, a scoping review by Chaudhry et al (2022) found that most research ethics committees in sub-Saharan Africa work under significant administrative and financial constraints. Additionally, in this issue, Brown (2023) describes how researchers affiliated to independent organisations and charities often do not have ready access to research ethics committees, unlike their counterparts who work within universities.…”
Section: Kate Chatfield and Edward Dovementioning
confidence: 99%